A lithospheric cross-section in the eastern Iberian Peninsula and its margins. Modelling the physical properties of the upper mantle - Carballo, Alberto; Fernández, Manel; Jiménez-Munto, Ivone (Física de la Tierra, 2012)
We study the lithosphere structure along a 1700 km transect crossing the Aquitaine basin, Pyrenees, Ebro basin, Catalan Costal Ranges, Valencia Trough, Balearic Promontory, and Sudbalearic basin, and Kabyles, Tell, Atlas, and Saharan Platform in Africa. The objective is to characterize the structure and composition of the lthospheric mantle in the region, using a method (LitMod) that combines elevation, gravity, geoid, surface heat flow, seismic and petrological data. Using this method we can identify along the profile different mantle composition, derived from geochemical analysis and age. This is the main different with the previous model done in the same area, where lithospheric mantle density just varied with temperature. The results obtained with the LitMod methodology show important differences in geometry and depth of the lithosphere-asthenosphere boundary with the previous model. In the present study we had to consider four different lithopheric mantle compositions in order to fit all the observables.